Mindfulness and eating behavior in adolescent girls at risk for developing type 2 diabetes - Annameier, Shelly K., author; Shomaker, Lauren B., advisor; Riggs, Nathan, committee member; Stallones, Lorann, committee member (Colorado State University. Libraries, 2017)
Mindfulness interventions to address disinhibited eating have increased in popularity. Yet, there is surprisingly limited research explicitly describing the relationship of mindfulness with disinhibited eating, particularly in adolescents. In theory, mindfulness may be inversely related to disinhibited eating because present-moment attention promotes an individual's ability to recognize and respond effectively to internal hunger and fullness cues, as well as to differentiate between physiological hunger signals and other internal or external stimuli for eating. The primary goal of this study was to evaluate the relationship of dispositional mindfulness to eating in the absence of hunger (EAH) in adolescent girls at risk for type 2 diabetes (T2D). The secondary objective was to evaluate the interactions among mindfulness, hunger state, and a propensity for loss-of-control eating (LOC) in the prediction of eating behaviors, both with and without hunger. Participants were 107 adolescent girls (12-17 years) from diverse racial/ethnic backgrounds. Adolescents self-reported dispositional mindfulness, were evaluated for LOC by validated interview, and participated in two successive, standardized laboratory test meals to assess eating when hungry from a buffet lunch and EAH from a snack array. Adolescents rated state appetite before and after the meal and snacks. In analyses adjusting for age (years), race/ethnicity, body composition (percent body fat, lean mass, and height), and depressive symptoms, mindfulness was inversely related to EAH. Accounting for similar covariates, meal energy intake was not affected by mindfulness, but instead was predicted by a significant interaction of state hunger by LOC. Girls with LOC and high hunger ate the most as compared to girls with LOC and lower hunger or to girls without LOC. Results from the current study suggest that mindfulness may play a role in more effective regulation of food intake in girls at-risk for T2D; however, a propensity for LOC eating may be particularly salient for overeating in a state of high hunger.